Quality Control and Assurance An Ancient Greek Term Re-Mastered - Kounis, Leo D. (IntechOpen, 2017)
Quality control and assurance cover a diverse area of modern life and play, undeniably, an important role. This book brings together a collection of international papers that showcase examples of current research and practice in industry and the medical profession. It is hoped that engineers, researchers and scientists will be assisted in their continuous quest for excelling in qualitative aspects. The Ancient Greek word arete means excellence or virtue and defines the highest qualitative state: a man's effectiveness and skill in goodness (optimum potentiae). Indeed, Ancient Greeks believed that without quality control, specifications are useless and may result to illegitimacy, which in turn may become a threat to society itself.